Pengembangan ternak Ruminansia terintegrasi di Desa Koto Simandolak Kabupaten Kuantan Singingi: Pemanfaatan kotoran ternak untuk biogas dan pupuk organik - Djaimi Bakce; Aras Mulyadi; Almasdi Syahza; Zulfan Saam; Adiwirman Adiwirman; Evy Rossi (Riau Journal of Empowerment, 2021)
Kuantan Singingi Regency is one of the ruminant-producing districts in Riau Province. Koto Simandolak Village, located in Benai District, Kuantan Singingi Regency, the majority of the people work as farmers. Generally, farmers in Koto Simandolak Village cultivate livestock traditionally, namely by releasing them to the wild. This condition causes several problems including livestock manure, pollution of the village environment, and conflicts with residents. This problem can be solved if the farmer wants to keep the cattle. By holding cattle, the manure will be collected directly in the cage. Animal manure can be processed and used in biogas and organic fertilizer. The Research and Community Services Team of Universitas Riau saw the potential for utilizing livestock manure waste in Koto Simandolak Village. The Team conducts training and assistance in the installation of biogas reactors as well as training and mentoring in the biogas production process using livestock manure. Another output of biogas production is organic fertilizer. The ultimate goal of this service activity is to increase the income of the target community, namely through increasing livestock production, biogas production, and organic fertilizer production.